Immunogenicity of chimeric hemagglutinins delivered by an orf virus vector platform against swine influenza virus - do Nascimento, Gabriela Mansano; de Oliveira, Pablo Sebastian Britto; Butt, Salman Latif; Diel, Diego G. (Frontiers in Immunology, 2024)
Orf virus (ORFV) is a large DNA virus that can efficiently deliver viral antigens in swine. Here we used ORFV as a vector platform to deliver chimeric hemagglutinins (HA) of Influenza A virus of swine (IAV-S). Vaccine development against IAV-S is hindered by the antigenic diversity of the IAV-S and the need for strain-specific immunity against strains circulating in the field. A promising alternative aiming at re-directing immune responses on conserved epitopes of the stalk segment of the hemagglutinin (HA2) has recently emerged. Sequential immunization with chimeric HAs comprising the same stalk but distinct exotic head domains can potentially induce cross-reactive immune responses against conserved epitopes of the HA2 while breaking the immunodominance of the head domain (HA1). Here, we generated two recombinant ORFVs expressing chimeric HAs encoding the stalk region of a contemporary H1N1 IAV-S strain and exotic heads derived from either H6 or H8 subtypes, respectively. The resulting recombinant viruses expressed the heterologous protein in vitro. Further, the immunogenicity and cross-protection of these vaccine candidates were assessed in swine after sequential intramuscular immunization with OV-cH6/1 and OV-cH8/1 viruses, and subsequent challenge with divergent IAV-S strains (Oh07, gamma clade and Ca09, pandemic clade). Humoral responses showed that vaccinated piglets presented increasing IgG responses in sera. Additionally, cross-reactive IgG and IgA antibody responses elicited by immunization were detected in sera and bronchoalveolar lavage (BAL), respectively, against different viral clades and a diverse range of contemporary H1N1 IAV-S strains, indicating induction of humoral and mucosal immunity in vaccinated animals. Importantly, viral shedding was reduced in nasal swabs from vaccinated piglets after intranasal challenge with IAV-S strain Oh07 , while viral load in lung and lung lesions were reduced in immunized groups independently of the challenge virus. Protection from severe lung pathology might be related to earlier viral clearance of the virus from lung tissues as suggested by lower replication rates in the lung and BAL. These results demonstrated the efficiency of ORFV-based vectors in delivering chimeric IAV-S HA-based vaccine candidates and underline the potential use of chimeric-HAs for prevention and control of influenza A in swine.